If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2p + 8 = 6 + -1(8p + 2) Reorder the terms: 8 + -2p = 6 + -1(8p + 2) Reorder the terms: 8 + -2p = 6 + -1(2 + 8p) 8 + -2p = 6 + (2 * -1 + 8p * -1) 8 + -2p = 6 + (-2 + -8p) Combine like terms: 6 + -2 = 4 8 + -2p = 4 + -8p Solving 8 + -2p = 4 + -8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '8p' to each side of the equation. 8 + -2p + 8p = 4 + -8p + 8p Combine like terms: -2p + 8p = 6p 8 + 6p = 4 + -8p + 8p Combine like terms: -8p + 8p = 0 8 + 6p = 4 + 0 8 + 6p = 4 Add '-8' to each side of the equation. 8 + -8 + 6p = 4 + -8 Combine like terms: 8 + -8 = 0 0 + 6p = 4 + -8 6p = 4 + -8 Combine like terms: 4 + -8 = -4 6p = -4 Divide each side by '6'. p = -0.6666666667 Simplifying p = -0.6666666667
| 9=7-2x | | -2+5x=16+8 | | 6x^4+6x-42=0 | | -6(2x-2)=-12x+12 | | 61=3v+10 | | 10x-8y-9z=0 | | 0.50(2x-6)=4(x-1) | | 21+6x=y | | 51=3.50p+5.50+6 | | x^2-50x+25=0 | | 2x+4y+3z=3 | | 21x^2y-15xy^2+9x^2y^2= | | -6n-(8n-5)=14-n | | x^2-6x=x(3+x) | | -6n-(8n-5)=14-2 | | w+13=10 | | d+9=35 | | a^2-48=0 | | 2x+10=8x+40 | | 7=y+6 | | 3x^2+2x+8=112 | | -15=-2+4m+7 | | -15=-2+4m+7 | | 8x-3=-2+4x | | Q+6=rt+2 | | -15=-2+4m+7 | | -9-5n=-44 | | 2x*5y=16 | | -4(8)-9=-23 | | 12-6x=2-4x | | 17.50+3.50x=125 | | -2=k+6-3k |